Respon Pertumbuhan Dan Hasil Tanaman Pakcoy (Brassica rapa L.) Akibat Pemberian Pupuk Organik Cair Urin Kelinci - Hayaturrohmah Asyakur; Nunung Sondari; Yana Taryana; Hudaya Mulyana (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2022)
The experiment was carried out in Cigargadung, Cigendel Village, Pamulihan District, Sumedang City, with an altitude of 794 meters above sea level with Latosol soil type. The experimental period starts from June – August 2021. The purpose of this study was to study the effect of the right concentration of liquid organic fertilizer in rabbit urine on the growth and yield of Pakcoy (Brassica rapa L) plants and to obtain the right concentration of liquid organic fertilizer on plant growth and yield. Pakcoy. The experimental design used was a randomized block design (RBD) with six treatments of rabbit urine concentration and repeated four times. The treatments were A = 0 ml L1 water (control), B = 2 ml L-1, C = 4 ml L-1, D = 6 ml L-1, E = 8 ml L-1, and F = 10 ml L-1. The results of the experiment showed that different administration of liquid organic fertilizer in rabbit urine had an effect on the growth and yield of pakcoy plants. The experimental results showed that giving treatment B = 2 ml L-1 LDP of rabbit urine had an effect on plant height growth of 35 DAP, number of leaves 21 DAP, leaf diameter 42 DAP, fresh weight 42 DAP, dry weight 42 DAP, and Root Decay Ratio 42 DAP. on pakcoy plants compared to other treatments.